Rethinking the Man-Land Relations in China (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue seeks to re-examine these changes in land relations in transitional China and rethink our understanding of human-environment interactions in both urban and rural areas, thus advancing theories in land-use science as a major component of land management and sustainability science.